Meta-analysis: the influence of learning styles on critical thinking of science learning - Hayat, Nor; Yuliani, Hadma; Nastiti, Luvia Ranggi (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
This study aims to investigate whether learning styles significantly affect the critical thinking ability of science learning students. The method in this study is a second-order integrative meta-analysis using many data sets from the results of previous research obtained from as many as 13 research journal articles with literature search using electronic databases using the keywords "Learning style", "Critical thinking", and "Science learning" conducted using the DOAJ, ERIC, Scopus, publish or perish 8.12 websites, research gate and Google Scholar in the form of international and national journals. This analytical study includes research comparing students' learning outcomes using different learning styles with quasi-experimental, experimental, and research and development methods. The results showed that there was a significant influence of learning style on the critical thinking ability of science learning students, with a representation obtained of 1.35 in the "high" category to conclude the effect of the effectiveness of the independent variable, namely the influence of learning style on the dependent variable critical thinking 88%.